Short Term Outcome of Preterm Neonates Required Mechanical Ventilation (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Since its inception, the neonatal mechanical ventilator has been considered an essential tool for managing preterm neonates with Respiratory Distress Syndrome (RDS) and is still regarded as an integral component in the neonatal respiratory care continuum. Mechanical ventilation of newborn has been practiced for several years with several advances made in the way. As compared to the western world and neighboring countries, neonatal ventilation in our country is still in its infancy. To analyze the common indications and outcome of preterm neonates required mechanical ventilation.Methods: This was a retrospective observational study conducted on preterm neonates required mechanical ventilation over a period of 12 months (July 2013 to June 2014).Results: A total of 50 neonates were mechanically ventilated during the study period of which 68% (n=34) survived. The survival rate was higher (77%) in 34-